Evaluasi Atas Pengendalian Intern Penjualan Dalam Upaya Meningkatkan Efektifitas Prosedur Penjualan - Marpaung, Annaria Magdalena (Jurnal Ilmiah Kesatuan (JIK), 2010)
Internal Control is one of the important things in company management, particularly to improve sales effectiveness. The goal of this research is to know how internal control in the company works and whether effort done by the company management can improve sale effectiveness. This research was done at PT AGRICON PUTRA CITRA OPTIMA TERMINIX, the company operates in service sector of pest exterminator by means of fumigation, termite baiting system (TBS), and chemical barrier system (CBS). The company is located in Bogor. This under-thesis arrangement has purposes for the author as well, namely to enlarge knowledge and to extend insight, especially about internal control system. In collecting data needed, the author did literature study related to the issues discussed. Besides, she carried out field study directly to the company that would be observed and examined. The results of this research shows that PT AGRICON PUTRA CITRA OPTIMA TERMINIX has worked well with internal control system. There has been separation of duties and functions of sale; and transaction process has been running well. In addition, the company has run internal control by questionnaire, narrative, and flowchart well; and it almost meet five components of internal control system in accordance with COSO. The selling system is arranged well and there are evidences to sale effectiveness.